From cellular information networks to digital molecular medicine (2008)
The emerging field of systems biology is transforming biotechnology to an extent that it is making individual investigators or even consolidated groups become obsolete, thereby making it necessary to work in global collaboration networks to be competitive. The new biology (as just another branch of information science) combined with genomics and proteomics is giving rise to personalised medicine at the molecular level and the ability to predict and prevent the risk of contracting major common diseases, as well as facilitating patients’ active participation or even that of healthy individuals in their own care. This so-called P4 medicine (predictive, preventative, personalised and participatory) essentially reflects people’s social life in informational biological molecules which are arranged in complex networks following a power law by which very few nodes or hubs made of either genes or their transcription and translation products dominate the entire network through unequal distribution of links or edges. Around one dozen publications of genome-wide association studies (GWAS) have shown how the genomic variations of some of these hubs can be applied to predicting the risk of contracting multigenic and common diseases. Moreover, combining GWAS with clinical and metabolic indices of risk significantly improves the power of such techniques for personalised medicine. Key words: Proteome; systems; networks; biotechnology; medicine